تحليل التركيب العمري والزواجي للسكان في سورية (مجلة جامعة اللاذقية- سلسلة العلوم الاقتصادية والقانونية, 2019)
يتناول هذا البحث دراسة التركيب العمري والزواجي للسكان والذي يعتبر من أهم الخصائص الديمغرافية التي يهتم بدراستها الباحث الديمغرافي والمخطط الاقتصادي والاجتماعي. ويهدف هذا البحث إلى تحليل التركيب العمري والزواجي للسكان للتعرف على التغيرات التي طرأت عليه خلال الفترة (1970-2000) والأسباب الكامنة وراء هذه التغيرات وأهم آثارها الاقتصادية والاجتماعية والديمغرافية. وقد توصلت هذه الدراسة إلى مجموعة من النتائج كانخفاض نسبة الأطفال من مجموع السكان، ولكن رغم الانخفاض الذي حصل في نسبة الأطفال إلا إنها ما زالت مرتفعة إذا ما قورنت مع مثيلاتها في الدول المتقدمة وإلى ارتفاع نسبة السكان في سن العمل ورغم هذا الارتفاع إلا أنها مازالت متدنية بالمقارنات الدولية. كما توصلت هذه الدراسة إلى أن نسبة العازبين قد ارتفعت، وأن نسبة السكان المتزوجين قد انخفضت خلال الفترة المدروسة (1981-1994). This research deals with age and marriage composition of population in Syria which is considered one of the most important demographic properties any demographic researcher is interested in, besides the social and the economical diagram. The aim of this research is to analyze age and marriage in the population in order to recognize the changes happened during the period from 1970 till 2000 and the potential reasons related to these changes, besides the most important social economical and demographic effect of these changes. The research reaches a set of results such as the decrease in the infant percentage and that despite of this fact, the percentage is still high compared to other developed countries besides the increase in the percentage of the working age population and that despite this fact it is still low compared to the international statistics. The research concludes that the percentage of single population increased while the percentage of married population decreased during the period of the study in the time from 1981 till 1994.